EVALUATION OF WORKSHIP AND STRATEGICS OF RIGHTS IN THE MSMEs IN THE DIGITAL AGE - M. Thoyyib; Januar Ida Wibowati; Martini (Adisam Publisher, 2024)
In today’s digital age, solid financial performance and strategic adaptation are becoming crucial to the survival of micro, small and medium-sized enterprises (MSMEs). The study aims to evaluate MSMEs financial performance and identify improvement strategies that can be applied in order to adapt to the challenges of the times. Through financial ratio analysis, including liquidity, solvency, profitability, and activity, we measure the operational efficiency of MSMEs and identify areas that need improvement. The method of research carried out is the study of literature by searching for references that correspond to the context of the research to be studied. Research results show that MSMEs that implement digital tools, such as social media, e-commerce, and online accounting systems, show significant improvements in financial performance compared to MSMEs that have not yet integrated digital technology. It shows that the presence of technology is a driving factor in strengthening market positions and increasing operational efficiency.